2018
DOI: 10.1111/nyas.13600
|View full text |Cite
|
Sign up to set email alerts
|

Triple surveillance: a proposal for an integrated strategy to support and accelerate birth defect prevention

Abstract: Preventing neural tube defects (NTDs) easily qualifies as a high‐value opportunity to improve childhood survival and health: the unmet need is significant (major preventable burden), the intervention is transformative (providing sufficient folic acid), and delivery strategies (e.g., fortification) are effective in low‐resource countries. Yet, NTD prevention is lagging. Can public health surveillance help fix this problem? Critics contend that surveillance is largely unnecessary, that limited resources are best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
(45 reference statements)
0
19
0
Order By: Relevance
“…However, a review of available information showed that many LMICs lack even basic data or vital registration systems capable of continuously generating reliable information on birth defects. This technical report considered a framework for surveillance specifically targeted at supporting and accelerating NTD prevention in LMICs …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a review of available information showed that many LMICs lack even basic data or vital registration systems capable of continuously generating reliable information on birth defects. This technical report considered a framework for surveillance specifically targeted at supporting and accelerating NTD prevention in LMICs …”
Section: Resultsmentioning
confidence: 99%
“…This technical report considered a framework for surveillance specifically targeted at supporting and accelerating NTD prevention in LMICs. 19 The ideal system ("triple surveillance") would collect information from cause to effect by integrating population surveillance of blood folate concentrations, NTD birth prevalence (among all pregnancy outcomes), and health outcomes in children born with NTDs (e.g., morbidity, mortality, disabil-ity, and quality of life). Different countries may be at different stages of preparedness and ability to implement such a surveillance system.…”
Section: Rethinking Surveillance For Ntd Preventionmentioning
confidence: 99%
“…Clearly, a most important factor is whether the mother of an affected baby had an optimal RBC folate (≥ 906 nmol/L) at the time of conception (Crider, Qi, Devine, Tinker, & Berry, 2018;Daly, Kirke, Molloy, Weir, & Scott, 1995). An ideal system would be that of triple surveillance (Botto & Mastroiacovo, 2018) where population surveys of RBC folate would be performed regularly, followed by NTD surveillance. The third surveillance activity would be assessing the long term outcome, including disability and quality of life.…”
Section: Folic Acidmentioning
confidence: 99%
“…The 63rd World Health Assembly resolution on birth defects has urged all member states to prioritize birth defects (WHO, ) and to “develop and strengthen registration and surveillance systems for birth defects within the framework of national health information systems in order to have accurate information available for taking decisions on prevention and control of these birth defects and to continue providing care and support to individuals affected by birth defects.” A recent consensus statement published by attendees of the 7th International Conference on Birth Defects and Developmental Disabilities in Developing World stressed the need to establish surveillance systems and improve data quality (Darmstadt, Howson, Walraven, et al, ). Botto and Mastroiacovo () proposed a novel concept of triple surveillance for NTDs, integrating surveillance of folate insufficiency, NTD prevalence, and health outcomes associated with NTDs. They state “By doing so, surveillance becomes not a roadblock but a preferential path to prevention and better care.” In a 2014 resolution, the Teratology Society called for global total prevention of folic acid‐preventable spina bifida and anencephaly by 2024 (Smith & Lau, ).…”
mentioning
confidence: 99%
“…A recent consensus statement published by attendees of the 7th International Conference on Birth Defects and Developmental Disabilities in Developing World stressed the need to establish surveillance systems and improve data quality (Darmstadt, Howson, Walraven, et al, 2016). Botto and Mastroiacovo (2018) proposed a novel concept of triple surveillance for NTDs, integrating surveillance of folate insufficiency, NTD prevalence, and health outcomes associated with NTDs. They state "By doing so, surveillance becomes not a roadblock but a preferential path to prevention and better care."…”
mentioning
confidence: 99%